Gold(I) complexes stabilized by nine- and ten-membered n-heterocyclic carbene ligands - Cervantes Reyes, Alejandro; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
Nine- and ten-membered N-heterocyclic carbene (NHC) ligands have been developed and for the first time their gold(I) complexes were synthesized. The protonated NHC pro-ligands 2 a-h were prepared by the reaction of readily available N,N′-diarylformamidines with bis-electrophilic building blocks, followed by anion exchange. In situ deprotonation of the tetrafluoroborates 2 a-h with tBuOK in the presence of AuCl(SMe2) provided fast access to NHC-gold(I) complexes 3-10. These new NHC-gold(I) complexes show very good catalytic activity in a cycloisomerization reaction (0.1 mol % catalyst loading, up to 100 % conversion) and their solid-state structures reveal high steric hindrance around the metal atom (%Vbur up to 53.0) which is caused by their expanded-ring architecture.